Developing Duel Chess Game As A Media In Learning Passive Voice - Liyyana Imatul Ukhrowiyyah (STKIP PGRI Trenggalek, 2021)
The objective of the research was to develop Duel Chess Game as a media in passive voice. The research design was educational research & development aimed at developing educational products. The second semester of eleventh-grade students in SMK Ar-Ridlwan Trenggalek academic year 2019/2020 consists of 26 female and 15 male students. The instruments that were used in this research was questionnaire, test, and interview. The data collected by questionnaire and test analyzed quantitative, and the interview was analyzed qualitatively. Need analysis score is 1056 where students agree that passive voice learning needs media. Duel Chess Game is very good and suitable as passive learning media, based on test; sig. (2-tailed) showed 0.000,0.05. So, H0 was rejected and Ha was accepted. In conclusion, Duel Chess Game is enough good and suitable as a media in learning passive voice.